Comparison of Corrosion Rate in the Environment of 10% Acetic Acid solution with different Deflection. - Nendi Suhendi Syafei; S S Rizki; Suryaningsih Suryaningsih; Darmawan Hidayat (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
The oil and gas industry exploration that will generally be followed by corrosive substances including sweet gas (eg H2S and CO2), it will result in corrosion event. The corrosion stress cracking will cause the carbon steel pipe to break so that production oil and gas can be stopped. The research aims in this paper is to analyze the corrosion event of carbon steel pipe in laboratory scale on acid environment with the existence of sweet gas H2O and CO2 by using three points loading method. This research uses carbon steel pipe API 5L-X65 which stay in condensation environment of 1350 ml aquades, 150 ml acetic acid. Based on the figure (5.a) and figure (5.b) that the corrosion rate will increase with increasing exposure time, and the greater the stress that is given, the corrosion rate increases according to the image (6.a) and image (6.b). Whereas based on the results of microstructural tests using optical microscopes, pitting corrosion occurs, and corrosion events occur are the stress corrosion cracking transgranular and intergranular based on figure 8.